Morin controls high-cholesterol diet-induced inflammatory cardiac dysfunction through the regulation of nitric oxide synthesized enzymes and P65 NF-κB gene: Effect of morin on hypercholesterolemia-induced cardiac changes - Aloud, Amal A. (Progress in Nutrition, 2019)
Morin is a natural yellow compound that is scientifically proven to have hypoglycemic, anti-inflammatory and anti-oxidant properties. The ameliorative effect of morin on high-cholesterol-diet (HCD) induced cardiac damage has not yet been assessed. Hence, in the present study, we evaluated the ability of the compound to controls HCD induced cardiac inflammation and oxidative damage through the regulation of nitric oxide synthesized enzymes and nuclear factor kappa B (P65 NF-κB) gene. HCD rats exhibited an increased activity of markers of cardiac enzyme in serum such as lactate dehydrogenase (LDH), creatine kinase-MB (CK-MB) and creatine kinase (CK). Administration of HCD to the rats was fond to elevate the serum and cardiac lipids profiles. Moreover, cardiac pro-inflammatory and cardiac oxidative markers were raised and the antioxidant markers were lowered. However, in the morin treated to HCD rats, the above markers for biochemical, inflammatory, antioxidants, and oxidative changes were reverted to near normal food consumed control rats. The myocardial protein expressions of neuronal nitric oxide, inducible nitric oxide, and endothelial nitric oxide synthases, as well as P65 NF-κB were significantly increased in rats supplemented with HCD. When treated with morin, these protein levels were lowered and were comparable to those of normal food consuming rats. Such an alleviated inflammatory myocardial dysfunction upon morin administration has been proven by the improvement of histological features. The results of this study suggest that morin administration combats HCD induced myocardial inflammation and dysfunction through the regulation of nitric oxide synthesized enzymes and P65 NF-κB gene. These results vouch for benefits of dietary morin against HCD induced cardiac dysfunction.